Blanking Clearance and Punch Velocity Effects on The Sheared Edge Characteristic in Micro-Blanking of Commercially Pure Copper Sheet - Didin Zakaria Lubis; Ichsan Ristiawan (Universitas Negeri Malang, 2017)
This study aims to identify the influences between clearance and punch velocity on the part edge quality of blanked parts. Experiments have been conducted using material copper, punch-die clearance and punch velocity variations. In order to determine the reachable punch-die clearance and punch velocity required for blanking. The quality of the part-edge characteristics shows that higher punch velocity and decreases clearance value can improve the part-edge quality, resulting in smaller burr height and rollover, and a larger shear zone. Furthermore, it could be observed that the part-edge quality improvement when blanking with high punch velocity is much more distinct for stele than for copper. According to blanking theory, this improvement was expected because copper have much higher heat conduction coefficients. Therefore, the heat dissipates faster and the desired stress relief effect does not take place to the same degree as for stele.